The role of myth in Plato’s Republic - Sacco, Gabriela Connell (My University, 2021)
In the Republic, Plato sets out his mistrust of myth and myth-makers, and the dangers that they pose to the good city. At the same time, the Republic reveals frequent references to myths and figures from traditional Greek mythology. The opposition between what Plato says and what he does creates a contradiction, which I seek to understand. My argument is situated in the view that Plato’s aim in writing his dialogues is to invite his reader to engage in the activity of philosophy. An important aspect of this is aporia, because aporia is the mindset in which philosophy begins. I argue that the reason that Plato makes use of myth in the Republic is because myths have the ability to induce distance in their audience, and this is an experience akin to aporia such that the audience is more open to experience aporia when they have already experienced a distance from the self. As such, Plato is able to use myth in his dialogue to further the aim of his work. Moreover, the tension between Plato’s stated orientation to myth and his actual use of myth has produced just the kind of perplexity that is the starting point of philosophy. The tension has produced aporia.
This dissertation is submitted in fulfilment of the requirements for the degree of Master of Arts by Research to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, 2021